"Vous venez d’où pour avoir cet accent ?" - Henri Boyer (Lengas)
From the combination of notions of speech community and linguistic market we search to highlight the impact of the imaginary of the French language community (ethno-socio-linguistic imaginary) on the dynamics of the official linguistic markets, considering as main driver a secular linguistic ideology : the unilingualism . This modeling, briefly exposed, is used to analyze the phenomenon of stigmatization / illegitimation suffered in France by the "accents" inconsistent with the dominant standard in this area and especially the "accent du Midi".